Systematic review of TNFα-induced paradoxical psoriasis: Treatment outcomes of switching to alternative biologic therapies in inflammatory bowel disease patients. (31st December 2023) - Revankar, Rishab; Patel, Heli; Rojas, Mary; Walsh, Samantha; McGee, Jean S.
Abstract: Objectives: The objective of this systematic review was to evaluate the efficacies of different biologic therapies in treating tumor necrosis factor-alpha (TNFα)-induced paradoxical psoriasis (PXP) and controlling inflammatory bowel disease (IBD) symptoms. Methods: We conducted a literature search of the Ovid EMBASE, Ovid Medline, Web of Science Core Collection, and Cochrane Central Register of Controlled Trials databases from their inception to October 3, 2021. We considered all peer-reviewed, randomized controlled trials, chart reviews, and observational studies that discussed the TNFα-induced PXP treatment outcomes in IBD patients of switching to different biologic therapies. Results: Switching to ustekinumab (UST) resulted in complete or partial resolution of TNFα-induced PXP in 83.1% of patients (74 out of 89 patients), while switching to either vedolizumab (VDZ) or secukinumab led to complete resolution in 100% of patients (eight out of eight patients). Approximately 75.4% of patients who were switched to UST remained in IBD remission, 4.6% in partial remission, and 20.0% in the flare of IBD. Conclusions: UST has sufficient data to demonstrate the efficacy in treating TNFα-induced PXP and controlling IBD symptoms concurrently. More data is needed to validate the efficacies of VDZ and SEC in treating TNFα-induced PXP in IBD patients.